2021
DOI: 10.1155/2021/6236135
|View full text |Cite
|
Sign up to set email alerts
|

Systematically Deciphering the Pharmacological Mechanism of Fructus Aurantii via Network Pharmacology

Abstract: Fructus Aurantii (FA) is a traditional herbal medicine that has been widely used for thousands of years in China and possesses a variety of pharmacological effects. However, the active ingredients in FA and the potential mechanisms of its therapeutic effects have not been fully explored. Here, we applied a network pharmacology approach to explore the potential mechanisms of FA. We identified 5 active compounds from FA and a total of 209 potential targets to construct a protein-protein interaction (PPI) network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…DEGs were extracted by comparing BEAS-2B cells (a he human bronchial epithelial cell line) before exposure to CS with after, and they are significantly enriched in the negative regulation of transferase activity (GO:0051348, adjusted p value = 2.21E−15) [ 54 ]. In addition, negative regulation of kinase activity (GO:0033673, adjusted p value = 1.57E−14), intracellular receptor signaling pathway (GO:0030522, adjusted p value = 3.78E−14), DNA-templated transcription, initiation (GO:0006352, adjusted p value = 1.57E−14), negative regulation of protein kinase activity (GO:0006469, adjusted p value = 2.25E−14) and transcription initiation from RNA polymerase II promoter (GO:0006367, adjusted p value = 1.10E−15) are the most enriched terms by GO enrichment analysis on key lung cancer-related gene sets that have been reported in other studies [ 55 59 ].…”
Section: Resultsmentioning
confidence: 58%
“…DEGs were extracted by comparing BEAS-2B cells (a he human bronchial epithelial cell line) before exposure to CS with after, and they are significantly enriched in the negative regulation of transferase activity (GO:0051348, adjusted p value = 2.21E−15) [ 54 ]. In addition, negative regulation of kinase activity (GO:0033673, adjusted p value = 1.57E−14), intracellular receptor signaling pathway (GO:0030522, adjusted p value = 3.78E−14), DNA-templated transcription, initiation (GO:0006352, adjusted p value = 1.57E−14), negative regulation of protein kinase activity (GO:0006469, adjusted p value = 2.25E−14) and transcription initiation from RNA polymerase II promoter (GO:0006367, adjusted p value = 1.10E−15) are the most enriched terms by GO enrichment analysis on key lung cancer-related gene sets that have been reported in other studies [ 55 59 ].…”
Section: Resultsmentioning
confidence: 58%
“…The active ingredients of black ants (XJ), Herba Epimedii (YYH), Fructus Lycii (SCZ) and Fructus Cnidii (GQZ) in the whole prescription were collected by the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and analysis platform ( http://lsp.nwu.edu.cn/tcmsp.php ), Traditional Chinese Medicine Integrated Database (TCMID, http://www . http://megabionet.org/tcmid ), Natural Products Database of Traditional Chinese Medicine of Shanghai Institute of Organic Chemistry ( http://www.chemcpd.csdb.cn ) and the related literature of the compound Xuanju capsule [ 21 , 22 ]. According to the integrative absorption, distribution, metabolism and excretion (ADME) model, bioavailability (OB) and drug-likeness (DL) were regarded as the screening criteria for active ingredients.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, they detected significant reductions in the numbers of neutrophils and macrophages in bronchoalveolar lavage fluid, which explains the significant anti-inflammatory effects of C. aurantium . Using a web-based pharmacological system, Jin et al [ 28 ] succeeded in resolving the pharmacological mechanism of C. aurantium and found that chuanpianin in C. aurantium has certain anti-inflammatory effects. Furthermore, Güvenç et al [ 29 ] examined the effects of tangerine in trifoliate aurantium (Figure 3 ) on the renal tissue of rats with renal ischemia-reperfusion injury and accordingly found that after the intervention with tangerine, there was a significant reduction in the levels of TNF-α and IL-1 expression in these rats, which were comparable to those detected in the control group rats.…”
Section: The Role Of Sanhua Decoction In the Prevention And Treatment...mentioning
confidence: 99%